Study on the Application of Healing Architecture in a Multi-Family Residential Building (Case Study: The Zora) - Iqbal, Muhammad; Sari, Yeptadian (Riviera Publishing, 2024)
Architecture is not only about physical development but also about creating an environment that supports the well-being of its residents. The concept of Healing Architecture has become an increasingly popular topic in recent years, focusing on the design and organization of spaces to support the health and well-being of their occupants. The concept of Healing Architecture is the concept of how the physical environment significantly impacts the mental and physical health of its residents. Compound residential buildings, often residences for many individuals and families, have great potential to apply the principles of Healing Architecture. However, research on the application of Healing Architecture in compound residential buildings is still limited. Therefore, this study aims to fill this knowledge gap by conducting an in-depth study of the application of Healing Architecture in compound residential buildings. This research will use a qualitative descriptive approach to understand how the principles of Healing Architecture are applied in the context of compound residential buildings. This method allows the research to explore and describe this phenomenon in detail and understand the influences and impacts that may arise from applying Healing Architecture in this context. The purpose of this research is to provide new and practical insights into how Healing Architecture can be applied in the design of compound residential buildings to support the welfare of its residents. The application of healing architecture principles in The Zora Area can be seen in the use of environmentally friendly materials, sufficient natural lighting, green open spaces, designs that support social interaction, and architectural elements that calm and reduce stress.